Pengaruh Return On Asset (ROA) terhadap return saham syariah dengan struktur modal sebagai variabel moderasi pada perusahaan manufaktur sektor industri barang konsumsi yang terdaftar di indeks saham syariah Indonesia periode 2015-2019 - Lorenza, Esmeralda; Zulkarnain, Deny; Joko, Lucius (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Along with the development of the Islamic financial system, the capital market has developed into an Islamic capital market that offers an attractive alternative compared to its conventional industry, which still relies on usury as its basic foundation. At the close of trading at the end of 2019, the shariah stock index recorded a higher growth than the Composite Stock Price Index (IHSG). The purpose of this study was to determine the effect of ROA on Shariah Stock Returns and the effect of Capital Structure in moderating the relationship between ROA and Shariah Stock Returns. The theories used in this research include Signalling Theory. The object in this study is a manufacturing company in the consumer goods industry which is listed on the ISSI. The technique of collecting data is by collecting secondary data in the form of stock price information and company annual financial reports. The sampling technique is a non-probability sampling technique with a purposive sampling method. The data analysis technique for testing this research is Moderated Regression Analysis (MRA) using the SPSS application. Based on the research conducted, it is found that Return on Assets has a significant effect on Shariah Stock Return in a positive direction. An increase in ROA can have an effect on increasing Stock Returns, and vice versa. Capital Structure is unable to moderate the relationship between ROA and Shariah Stock Return.